Effect of curing condition and carbonization enhancement on mechanical properties of fly ash -desulfurization gypsum - steel slag blocks. Issue 38 (May 2020) - Duan, Siyu; Liao, Hongqiang; Cheng, Fangqin; Tao, Mingjiang
Highlights: The FA-SS-FGD gelation block was cured by the hot and humid+autoclave combined curing condition, and its compressive strength reached 35.8MPa in a short time. The hot and humid autoclave curing was favorable for producing more C-S-H gels and promoting the conversion of C-S-H gels to tobermorite crystals on the gelation block. The gelation block is soaked in saturated lime water and then carbonized, improving the compressive strength of the test block and simultaneously absorbing CO2 . Abstract: This research demonstrates the effect of curing conditions and carbonization enhancement on mechanical properties of fly ash (FA) - desulfurization gypsum (FGD) - steel slag (SS) gelation blocks. Five curing conditions, including dry-air curing, hot and humid curing, autoclave curing, hot and humid+autoclave curing, autoclave+hot and humid curing, were studied. The experimental results showed that the gelation block under the hot and humid+autoclave curing condition had the highest compressive strength, reaching 35.8MPa. The microstructural characterization of the gelation block by X-ray diffraction (XRD), Fourier-transfer infrared spectroscopy (FT-IR), Thermogravimetric analysis (TGA) and Scanning electron microscopy (SEM) indicated that the hot and humid + autoclave curing was favorable for producing more C-S-H gels and promoting the conversion of C-S-H gels to tobermorite crystals on the gelation block. Under the hot and humid+autoclave curing condition, both the tobermorite crystals and C-S-H gels resulted in more compact gelation blocks and thus their higher mechanical properties. The cured gelation block was subjected to enhanced carbonation, which resulted in a more compact gelation block with its pores filled with nano-size calcium carbonate and thus further improvement in its compressive strength by 19.6 %. The physical effect of enhanced carbonation on the gelation block is increased mass by 1.95 %, indicating that approximately 1.95 % of CO2 of the mass of the respective gelation block can be absorbed.